The importance of feeding in the larval development of the ghost shrimp Callichirus major (Decapoda: Callianassidae) - ABRUNHOSA, Fernando Araujo (2011)
The present study investigated whether the callianassid Callichirus major shows a lecithotrophic behaviour during larval development. Two experiments were carried out. In the first experiment, larvae were subjected to an initial period of feeding, while in the second they were subjected to an initial period of starvation. In Experiment 1, 80% of C. major larvae succeeded moulting to juvenile stage in treatment with larvae fed every day. In the treatments with larvae fed for 1, 2 and 3 days there was total mortality before they reached the megalopal stage. In Experiment 2, zoea larvae showed more resistance when subjected to an initial period of starvation in which larvae starved for 1, 2 and 3 days and had survival rates of 100, 60 and 80%, respectively. But, a delay in the development duration of the zoeal stages was observed. Total mortality was observed for larvae reared in the treatment with entire starvation. The results suggest that zoeal stages of C. major are not lecithotrophic.